2020
DOI: 10.1371/journal.pone.0230419
|View full text |Cite
|
Sign up to set email alerts
|

Secondary spontaneous pneumothorax and bullous lung disease in cannabis and tobacco smokers: A case-control study

Abstract: Background The notion that smoking cannabis may damage the respiratory tract has been introduced in recent years but there is still a paucity of studies on this subject. The aim of this study was to investigate the relationship between cannabis smoking, pneumothorax and bullous lung disease in a population of operated patients. Methods and findings We performed a retrospective study on patients operated on for spontaneous pneumothorax. Patients were divided into three groups according to their smoking habit: c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…216 217 Cannabis smoking has also been associated with pneumothorax, 218 and combining cannabis use with tobacco use may increase this risk. 219 However, in general, cannabis use does not appear to be associated with emphysema. 103 205 213…”
Section: Long-term Cannabis Exposurementioning
confidence: 97%
“…216 217 Cannabis smoking has also been associated with pneumothorax, 218 and combining cannabis use with tobacco use may increase this risk. 219 However, in general, cannabis use does not appear to be associated with emphysema. 103 205 213…”
Section: Long-term Cannabis Exposurementioning
confidence: 97%
“…A prospective study supports the correlation between marijuana abuse and primary spontaneous pneumothorax [10]. A case-controlled study by Stefani et al revealed that cannabis smokers are at significant risk of developing bullous lung disease and have a higher incidence of tension pneumothorax compared to both tobacco smokers and nonsmokers [9].…”
Section: Discussionmentioning
confidence: 78%
“…The harmful pulmonary consequences of chronic marijuana smoking are less well documented than those of tobacco smoking. Spontaneous pneumothorax has been described as a long-term consequence, but most reported cases are of patients who combined tobacco and cannabis, which makes it difficult to see the direct causational effects of long-term marijuana abuse on the lungs [6][7][8][9]. Our patient smokes marijuana heavily without tobacco, which gives us a chance to highlight its effect on the lungs and its potential to cause bullous lung disease leading to spontaneous pneumothorax.…”
Section: Introductionmentioning
confidence: 90%
“…We performed pleural abrasions with resection and application of glue. In our study persistent air leak after surgical intervention was 0% to 10 % without significant in both groups but chest tube removal after operation was range [3][4][5] to [3][4][5][6] days for group A to group B respectively with highly significant p value [0.006].…”
Section: Discussionmentioning
confidence: 86%
“…Primary spontaneous pneumothorax [PSP] is a condition occurring more commonly in tall, athletic, smoker younger patients usually without underlying lung disease [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%